Draft Genome Sequence of the Shrimp Pathogen Vibrio parahaemolyticus ST17.P5-S1, Isolated in Peninsular Malaysia - Devadas, Sridevi; Bhassu, Subha; Soo, Christie Tze Chiew; Yusoff, Fatimah M.; Shariff, Mohamed; Maresca, Julia (American Society for Microbiology, 2018)
We sequenced the genome of Vibrio parahaemolyticus strain ST17.P5-S1, isolated from Penaeus vannamei cultured in the east coast of Peninsular Malaysia. The strain contains several antibiotic resistance genes and a plasmid encoding the Photorhabdus insect-related (Pir) toxin-like genes, pirAvp and pirBvp, associated with acute hepatopancreatic necrosis disease (AHPND).